2010
DOI: 10.1007/s00213-010-2053-y
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant-like effect of the 3β-hydroxysteroid dehydrogenase inhibitor trilostane involves a regulation of β-type estrogen receptors

Abstract: These data demonstrate that the antidepressant-like potential of trilostane is not due to its 3β-HSD inhibiting activity, since it is not shared by cyanoketone, but rather to its estrogenic activity. The compound, which releases estradiol and up-regulates ERβ receptors, could be used as a therapeutic tool to allow an estrogenic facilitation of antidepressant efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“… 26 Antidepressant treatment relieves HPA-axis hyperactivity and improves levels of monoamine neurotransmitter. 50 , 51 In the present study, we found that Zuotai could significantly reverse HPA-axis hyperactivity at doses of 6.0697 and 60.697 mg⋅kg −1 by reducing serum CRH, ACTH, and Cort levels. Furthermore, we observed that Zuotai could remarkably upregulate the level of monoamine neurotransmitters (5-HT and NE).…”
Section: Discussionsupporting
confidence: 57%
“… 26 Antidepressant treatment relieves HPA-axis hyperactivity and improves levels of monoamine neurotransmitter. 50 , 51 In the present study, we found that Zuotai could significantly reverse HPA-axis hyperactivity at doses of 6.0697 and 60.697 mg⋅kg −1 by reducing serum CRH, ACTH, and Cort levels. Furthermore, we observed that Zuotai could remarkably upregulate the level of monoamine neurotransmitters (5-HT and NE).…”
Section: Discussionsupporting
confidence: 57%
“…There is interest in developing agents, such as basimglurant and fenobam, as antidepressants and anxiolytics that target glutamatergic receptors 46. Estrogen Receptor 2 ( ESR2 ) has previously been implicated in antidepressant action through up-regulation by 3β-hydroxysteroid dehydrogenase 47. Estrogenic compounds have also been found to have antidepressant effects in rodent models of depression 48.…”
Section: Discussionmentioning
confidence: 99%
“…There is interest in developing agents, such as basimglurant and fenobam, as antidepressants and anxiolytics that target glutamatergic receptors 82 . Estrogen Receptor 2 ( ESR2 ) has previously been implicated in antidepressant action through up-regulation by 3β-hydroxysteroid dehydrogenase 83 . Estrogenic compounds have also been found to have antidepressant effects in rodent models of depression 84 .…”
Section: Discussionmentioning
confidence: 99%